A Parametric Approach for Spectrum Analysis and Carrier Frequency Estimation of Search and Rescue Satellite-Aided Tracking (SARSAT) Signals - El-Hennawey, Samy Mohamed (My University, 1985)
This thesis deals with the analysis of emergency locator transmitter (ELT) signals used for locating crash sites of aircraft or ships through the Search and Rescue Satellite Aided Tracking (SARSAT) System. This system uses the doppler shift phenomenon to achieve its goal.
Experiments conducted by the Communications Research Centre (CRC) in Ottawa, discovered problems associated with a family of ELT units produced by certain manufacturers. One of the major problems is the random-phase characteristic of these ELT signals, producing bad spectra, where the doppler shift cannot be easily estimated.
In this thesis, the performance of different processors, including the Periodogram (FFT) and the autoregressive moving average (ARMA) method, is investigated as applied to estimating the spectrum of ELT signals. The spectrum is used to obtain the doppler shift. Results of processing computer-generated signals and real test ELT signals indicate the inefficiency of the FIT for random phase signals. However, low order ARMA models are seen to be more effective.
A novel processor is suggested here for handling the random-phase signals. This processor is based on a new approach (proposed here) for carrier frequency estimation of signals, using low order MEM or ARMA. Not only is random phase problem solved, but also simplified processing and more accurate results can be achieved.
Keywords: Electrical and Computer Engineering; Electrical and Computer Engineering